Assessing the long-term hydrological services provided by wetlands under changing climate conditions: A case study approach of a Canadian watershed - Fossey, Maxime; Rousseau, Alain N. (Journal of Hydrology, 2016)
The water content of wetlands represents a key driver of their hydrological services and it is highly dependent on short- and long-term weather conditions, which will change, to some extent, under evolving climate conditions. The impact on stream flows of this critical dynamic component of wetlands remains poorly studied. While hydrodynamic modelling provide a framework to describe the functioning of individual wetland, hydrological modelling offers the opportunity to assess their services at the watershed scale with respect to their type (i.e., isolated or riparian). This study uses a novel approach combining hydrological modelling and limited field monitoring, to explore the effectiveness of wetlands under changing climate conditions. To achieve this, two isolated wetlands and two riparian wetlands, located in the Becancour River watershed within the St Lawrence Lowlands (Quebec, Canada), were monitored using piezometers and stable water isotopes (δD – δ18O) between October 2013 and October 2014. For the watershed hydrology component of this study, reference (1986–2015) and future meteorological data (2041–2070) were used as inputs to the PHYSITEL/HYDROTEL modelling platform. Results obtained from in-situ data illustrate singular hydrological dynamics for each typology of wetlands (i.e., isolated and riparian) and support the hydrological modelling approach used in this study. Meanwhile, simulation results indicate that climate change could affect differently the hydrological dynamics of wetlands and associated services (e.g., storage and slow release of water), including their seasonal contribution (i.e., flood mitigation and low flow support) according to each wetland typology. The methodological framework proposed in this paper meets the requirements of a functional tool capable of anticipating hydrological changes in wetlands at both the land management scale and the watershed management scale. Accordingly, this framework represents a starting point towards the design of effective wetland conservation and/or restoration programs.
Keywords: Rousseau_Alain

Assessment of the impact of spatio-temporal attributes of wetlands on stream flows using a hydrological modelling framework: a theoretical case study of a watershed under temperate climatic conditions - Fossey, Maxime; Rousseau, Alain N.; Savary, Stéphane (Hydrological Processes, 2016)
Wetlands play a significant role on the hydrological cycle, reducing flood peaks through water storage functions and sustaining low flows through slow water release ability. However, their impacts on water resources availability and flood control are mainly driven by wetland type (e.g., isolated wetland –IW- and riparian wetland –RW-) and location within a watershed. Consequently, assessing the qualitative and quantitative impact of wetlands on hydrological regimes has become a relevant issue for scientists as well as stakeholders and decision-makers. In this study, the distributed hydrological model, HYDROTEL, was used to investigate the role and impact of the geographic distribution of isolated and riparian wetlands on stream flows of the Becancour River watershed of the St Lawrence Lowlands, Quebec, Canada. The model was set up and calibrated using available datasets (i.e., DEM, soil, wetland distribution, climate, land cover, and hydrometeorological data for the 1969-2010 period). Different Wetland Theoretical Location Tests (WTLT) were simulated. Results were used to determine whether stream flow parameters, related to peak flows and low flows, were related to: (i) geographic location of wetlands, (ii) typology of wetlands, and (iii) seasonality. The contribution of a particular wetland was assessed using intrinsic characteristics (e.g., surface area, typology) and extrinsic factors (e.g., location in the watershed landscape and seasonality). Through these investigations, the results suggest, to some extent, that both IWs and RWs impact landscape hydrology. The more IWs are located in the upper part of the watershed, the greater their effect on both on high flow damping and low flow support seems to be. The more RWs are connected to a main stream, the greater their effect is. Our modelling results indicate that local landscape conditions may influence the wetland effect; promoting or limiting their efficiency, and thus their impacts on stream flows depend on a combined effect of wetland and landscape attributes.
Keywords: Rousseau_Alain

Integrating isolated and riparian wetland modules in the PHYSITEL/HYDROTEL modelling platform: model performance and diagnosis - Fossey, Maxime; Rousseau, Alain N.; Bensalma, Fatima; Savary, Stéphane; Royer, Alain (Hydrological Processes, 2015)
Mathematical modelling is a well-accepted framework to evaluate the effects of wetlands on stream flow and watershed hydrology in general. Although the integration of wetland modules into a distributed hydrological model represents a cost-effective way to make this assessment, the added value brought by landscape-specific modules to a model's ability to replicate basic hydrograph characteristics remains unclear. The objectives of this paper were to: (i) present the adaptation of PHYSITEL (a GIS) to parameterize isolated and riparian wetlands; (ii) describe the integration of specific isolated wetland and riparian wetland modules into HYDROTEL, a distributed hydrological model; and (iii) evaluate the performance of the updated modelling platform with respect to the capacity of replicating various hydrograph characteristics. To achieve this, two sets of simulations were performed (with and without wetland modules) and the added-value was assessed at three river segments of the Becancour River watershed, Quebec, Canada, using six general goodness-of-fit indicators (GOFIs) and fourteen water flow criteria (WFC). A sensitivity analysis of the wetland module parameters was performed to characterize their impact on stream flows of the modelled watershed. Results of this study indicate that: (i) integration of specific wetland modules can slightly increase the capacity of HYDROTEL to replicate basic hydrograph characteristics and (ii) the updated modelling platform allows for the explicit assessment of the impact of wetlands (e.g., typology, location) on watershed hydrology.
Keywords: Rousseau_Alain